The Search for an Exit from the Dictatorship and the Transformation of Greek Conservatism, 1967-1974 - Rizas, Sotiris (The Historical Review/La Revue Historique, 2014)
The purpose of this paper is to examine the process of transformation of Greek conservatism that evolved during the dictatorship from a current identified with the restrictive practices of the post-Civil War political system to a tenet of the democratic regime established in 1974. The realization that the military coup was not just the manifestation of anti-communism, the dominant ideology of the post-Civil War period, but also of an anti-parliamentary spirit permeating the armed forces, the prolongation of military rule that led to the crystallization of differences between the military regime and the conservative political class and an apprehension that the dictatorship might fuel uncontrollable social and political polarization are three inter-related factors that explain this transformation.